Amyand's hernia: a case report and literature review - Zhang, Li; Chen, Zihan; Fu, Yanxiang; Zhang, Qi; Hu, Hailong (Frontiers in Pediatrics, 2025)
Amyand's hernia (AH), an extremely rare form of inguinal hernia, particularly those cases where the hernial sac contains an inflamed, edematous, or perforated appendix, is infrequently encountered. This report details the case of a 6-year-old boy who presented with an irreducible, painful mass in the right inguinal region of unknown etiology. A CT scan indicated right inguinal hernia, and a blood routine test revealed elevated white blood cell counts. The patient was diagnosed with right inguinal hernia (AH) and acute appendicitis. Emergency laparoscopic high ligation of the inguinal hernia sac and appendectomy were performed. A postoperative pathological examination confirmed acute simple appendicitis and periappendicitis. The patient recovered uneventfully and was discharged 5 days after surgery. With a 6-month follow-up, no recurrence was observed, and the patient remains under follow-up. In conclusion, AH is a rare condition, and laparoscopic high ligation of the hernial sac is the primary treatment approach. During surgery, careful identification of the hernia contents is essential. Comprehensive preoperative assessment, precise surgical techniques, and standardized intraoperative and postoperative management play a vital role in minimizing complications and reducing the risk of postoperative recurrence.